2020
DOI: 10.1038/s41598-020-76540-1
|View full text |Cite
|
Sign up to set email alerts
|

In situ formation of photoactive B-ring reduced chlorophyll isomer in photosynthetic protein LH2

Abstract: Natural chlorophylls have a D-ring reduced chlorin π-system; however, no naturally occurring photosynthetically active B-ring reduced chlorins have been reported. Here we report a B-ring reduced chlorin, 17,18-didehydro-bacteriochlorophyll (BChl) a, produced by in situ oxidation of B800 bacteriochlorophyll (BChl) a in a light-harvesting protein LH2 from a purple photosynthetic bacterium Phaeospirillum molischianum. The regioselective oxidation of the B-ring of B800 BChl a is rationalized by its molecular orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Near the time of submission of this manuscript, chemical oxidation of the exposed ring D of the B 800 BChl a molecules of isolated light-harvesting complexes (LH2) from Phaeospirillium molischianum was reported. 61 The spectrum of the LH2 BChl a oxidation product in methanol shows a 7 nm bathochromic shift of the Q y band relative to that for 3-AcChl a and is identical to the spectrum obtained here for Chl X in methanol (Figure 6 and Figure S1-7D).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Near the time of submission of this manuscript, chemical oxidation of the exposed ring D of the B 800 BChl a molecules of isolated light-harvesting complexes (LH2) from Phaeospirillium molischianum was reported. 61 The spectrum of the LH2 BChl a oxidation product in methanol shows a 7 nm bathochromic shift of the Q y band relative to that for 3-AcChl a and is identical to the spectrum obtained here for Chl X in methanol (Figure 6 and Figure S1-7D).…”
supporting
confidence: 76%
“…Absorption spectra of samples in methanol from this study (gold and green) and from ref (black dashed) for (A) 3-AcChl a and (B) Chl X from this study and oxidized LH2 B800 BChl a (e.g., 17,18-didehydro BChl a ) from ref . Also shown are structures of 3-AcChl a (i.e., 7,8-didehydro BChl a ) (top right) in which ring B of BChl a is oxidized and of 17,18-didehydro BChl a (bottom right) in which ring D of BChl a is oxidized.…”
Section: Results and Discussionmentioning
confidence: 91%
“…molischianum and Mch. purpuratum , this absorption band is blue shifted to 846 nm ( 14 ) and 828 nm, respectively (fig. S7).…”
Section: Discussionmentioning
confidence: 96%
“…One strategy for this is the attachment of energy-donating dyes to the polypeptides of target complexes. Recent reports on chemical modifications of LH2 with artificial dyes indicated that the modified LH2 had two kinds of energy donors to B850 and unique EET dynamics among the two donors and the acceptor (B850). , Such LH2 variants would be good candidates for recently developing spectroscopies such as two-dimensional electronic spectroscopy. The substitution of native BChl a with other pigments in LH2 proteins is another promising strategy for changing the energy donor in LH2 proteins, and time-resolved spectroscopy of B800-substituted LH2 variants was performed. ,,, In situ oxidation of B800 BChl a is also useful for engineering LH2 proteins. , The direct conversion of B800 BChl a into Chl pigments is advantageous for facile preparation of LH2 variants containing two types of energy-donating (B)­Chls in the B800 sites and provides new insights into the excited-state dynamics of chromophores in the B800 sites.…”
Section: Introductionmentioning
confidence: 99%